Functional Cellular Mimics for the Spatiotemporal Control of Multiple Enzymatic Cascade Reactions - Liu, Xiaoling; Formanek, Petr; Voit, Brigitte; Appelhans, Dietmar (Angewandte Chemie International Edition, 2017)
Next-generation therapeutic approaches are expected to rely on the engineering of biomimetic cellular systems that can mimic specific cellular functions. Herein, we demonstrate a highly effective route for constructing structural and functional eukaryotic cell mimics by loading pH-sensitive polymersomes as membrane-associated and free-floating organelle mimics inside the multifunctional cell membrane. Metabolism mimicry has been validated by performing successive enzymatic cascade reactions spatially separated at specific sites of cell mimics in the presence and absence of extracellular organelle mimics. These enzymatic reactions take place in a highly controllable, reproducible, efficient, and successive manner. Our biomimetic approach to material design for establishing functional principles brings considerable enrichment to the fields of biomedicine, biocatalysis, biotechnology, and systems biology.
CRIS-Team Scopus Importer:2022-04-14
Keywords: cell mimics; enzyme catalysis; metabolism; polymersomes; synthetic biology